2017
DOI: 10.1021/acs.jpcb.6b12339
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental and Molecular Simulation Study of Factors Influencing the Selection of Antioxidants in Butadiene Rubber

Abstract: For the selection of antioxidants, internal factors were proposed by analyzing the thermal-oxidative aging process, which consisted of the following two inseparable steps: (1) the physical process of oxygen (O) entering the rubber network and (2) the complex chemical process of O reacting with the rubber network. Antioxidants 2246, 6PPD, and MB, examples of amines, phenols, and heterocycles, respectively, were chosen to study these factors influencing the selection of antioxidants for the thermal-oxidative agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…Solubility parameter (δ) was a useful parameter to predict the compatibility of two components. Empirically, for two materials A and B , if the absolute difference of the solubility parameters (Δδ = |δ A − δ B |) is <2.05 (J/cm 3 ) 0.5 , the two components are compatible; if Δδ is between 2.05 and 6.95 (J/cm 3 ) 0.5 , they are partially compatible; if Δδ is larger than 10.02 (J/cm 3 ) 0.5 , they are incompatible . So, the δs of NBR230S and four hindered phenols (listed in Table ) were first calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Solubility parameter (δ) was a useful parameter to predict the compatibility of two components. Empirically, for two materials A and B , if the absolute difference of the solubility parameters (Δδ = |δ A − δ B |) is <2.05 (J/cm 3 ) 0.5 , the two components are compatible; if Δδ is between 2.05 and 6.95 (J/cm 3 ) 0.5 , they are partially compatible; if Δδ is larger than 10.02 (J/cm 3 ) 0.5 , they are incompatible . So, the δs of NBR230S and four hindered phenols (listed in Table ) were first calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The shear testing parameters were as follows: temperature: 25 • C, sample deformation rate: 10 rad/s, stress: from 0.1% to 150%, test force: 10 N. The Payne effect was performed for filled vulcanizates and compared with the reference sample. The Payne effect values (∆G') for composites were calculated from the Equation (7):…”
Section: Payne Effectmentioning
confidence: 99%
“…The participation of individual units is important for the chemical structure of BR, and thus for its functional properties [4,5]. Vulcanizates made of stereospecific BR (showing a high regularity of structure) have a low hysteresis, and thus a low coefficient of friction, high abrasion resistance and good dynamic properties [6][7][8]. Additionally, due to its low glass transition temperature (T g ~105 • C), compared to the styrene-butadiene rubber (SBR) or natural rubber (NR), this rubber is preferred, in particular, for the production of tires with low rolling resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients showed a decreasing trend from BIIR-1# to BIIR-3#, which suggested that the gas permeability gradually increased with the increase in the bromine content. As reported earlier, − the diffusion of small molecular gas in polymer materials is extremely sensitive to free volume. After IIR was brominated to form BIIR, a certain amount of bromine atoms was introduced into the IIR molecular chain.…”
Section: Resultsmentioning
confidence: 53%